Developing a structured education reminiscence‐based programme for staff in long‐stay care facilities in Ireland. Issue 13 (14th December 2012) - Cooney, Adeline; O'Shea, Eamon; Casey, Dympna; Murphy, Kathy; Dempsey, Laura; Smyth, Siobhan; Hunter, Andrew; Murphy, Edel; Devane, Declan; Jordan, Fionnuala
<x xml:space="preserve">Abstract</x> Aims and objectives This paper describes the steps used in developing and piloting a structured education programme – the Structured Education Reminiscence‐based Programme for Staff (SERPS). The programme aimed to prepare nurses and care assistants to use reminiscence when caring for people with dementia living in long‐term care. Reminiscence involves facilitating people to talk or think about their past. Background Structured education programmes are used widely as interventions in randomised controlled trials. However, the process of developing a structured education programme has received little attention relative to that given to evaluating the effectiveness of such programmes. This paper makes explicit the steps followed to develop the SERPS, thereby making a contribution to the methodology of designing and implementing effective structured education programmes. Design The approach to designing the SERPS was informed by the Van Meijel et al. (2004) model (Journal of Advanced Nursing 48, 84): (1) problem definition, (2) accumulation of building blocks for intervention design, (3) intervention design and (4) intervention validation. Methods Grounded theory was used (1) to generate data to shape the 'building blocks' for the SERPS and (2) to explore residents, family and staff's experience of using/receiving reminiscence. Results Analysis of the pilot data indicated that the programme met its objective of preparing staff to use reminiscence with residents with dementia. Staff were positive both about the SERPS and the use of reminiscence with residents with dementia. Conclusions This paper outlines a systematic approach to developing and validating a structured education programme. Participation in a structured education programme is more positive for staff if they are expected to actively implement what they have learnt. Ongoing support during the delivery of the programme is important for successful implementation. Relevance to clinical practice The incorporation of client and professional experience in the design phase is a key strength of this approach to programme design.